Access to enantioenriched 4-phosphorylated δ-lactones from β-phosphorylenones and enals via carbene organocatalysis. Issue 52 (28th May 2020) - Verma, Ram Subhawan; Khatana, Anil Kumar; Mishra, Monika; Kumar, Shailesh; Tiwari, Bhoopendra
Abstract : N-heterocyclic carbene (NHC) catalyzed direct access to enantioenriched 4-phosphorylated δ-lactones from β-phosphorylenones and enals has been achieved. Abstract : N-heterocyclic carbene (NHC) catalyzed direct access to enantioenriched 4-phosphorylated δ-lactones from β-phosphorylenones and enals has been achieved. The sterically demanding β-phosphonate-substituted enones, having competing regiomeric reaction centres, have remained elusive so far in intermolecular cycloaddition reactions under NHC catalysis. All the products were obtained in excellent yield and enantioselectivity. These phosphorylated δ-lactones could be transformed into challenging multi-functionalized chiral esters and amides loaded with a β-ketophosphonate functionality.